Optimization of bacterial cellulose production by using response surface methodology(RSM)effect of PH,temperature and concentration of fermentation medium - Muhammad Azlan, Nazeri (2012)
Bacterial cellulose is a type of biopolymer that produced by Acetobacter xylinum in high purity,high water holding capacity,good mechanical strength, elasticity and high crystallinity.In this research,pineapple residue was used as the carbon sources to replace the pure carbon sources as the substrate for the synthesis of bacterial cellulose.The objective of this study was to investigate the effect of temperature,pH and concentration in the production of bacterial cellulose by Acetobacter xylinum.The important part in this research,including of preparation HS-Medium and agar plate as a medium for breeding the stock culture that was taken from Malaysia Agricultural Research and Development Institute (MARDI),Serdang,Selangor.Ideal condition in this research that investigated was varied from 40% to 100% for the concentration while the temperature was between 28°C to 32°C and pH were 4.5 to 8.5.Besides,this is study also aims to optimize the production of bacterial cellulose from pineapple residue using response surface methodology (RSM) based on the central composite design (CCD).Before RSM is used,the known value of the parameters was estimated based on one factor at that time (OFAT).The results obtained from the OFAT showed the optimum condition at pH 5.50,temperature 30°C and concentration of pineapple residue was 80 % where the amount of dry weight bacterial cellulose produced was 3.3948 g.According to the RSM result, the optimal set cultural conditions for bacterial cellulose were pH 5.15,temperature 30.51°C and concentration of pineapple residue was 83.32%.Bacterial cellulose production of 3.4368 g was achieved by using these optimal conditions. The existence of bacterial cellulose was proven by Fourier Transform Infrared (FT-IR) Spectroscopy analysis based on the appearance of absorbance peak for the C-C bonding, C-O bonding,C-OH bonding and C-O-C bonding.In addition,Scanning Electron Microscopy (SEM) was used to observe surface and cross section of the bacterial cellulose film.In short,the data presented in this paper showed that pineapple residue has a great potential as the carbon source in production of bacterial cellulose.